Worker Identity, Employment Fluctuations and Stabilization Policy - Dennis J. Snower; Wolfgang Lechthaler (Institute for the Study of Labor (IZA), 2013)
This paper provides a model of social hysteresis whereby long, deep recessions demotivate workers and thereby lead them to change their work ethic. In switching from a pro-work to an anti-work identity, their incentives to seek and retain work fall and consequently their employment chances fall. In this way, temporary recessions may come to have permanent effects on aggregate employment. We also show that these permanent effects, along with the underlying identity switches, can be avoided through stabilization policy. The size of the government expenditure multiplier can be shown to depend on the composition of identities in the workforce.
Keywords: E24; E60; J21; J28; 330; economics of identity; work ethic; hysteresis; business cycle policy; Arbeitslosigkeit; Arbeitsethik; Hysteresis; Konjunktur; Beschäftigungsfähigkeit; Konjunkturpolitik; Theorie